A comprehensive review of speech emotion recognition systems - Wani, Taiba Majid; Gunawan, Teddy Surya; Ahmad Qadri, Syed Asif; Kartiwi, Mira; Ambikairajah, Eliathamby (IEEE, 2021)
During the last decade, Speech Emotion Recognition (SER) has emerged as an integral component within Human-computer Interaction (HCI) and other high-end speech processing systems. Generally, an SER system targets the speaker’s existence of varied emotions by extracting and classifying the prominent features from a preprocessed speech signal. However, the way humans and machines recognize and correlate emotional aspects of speech signals are quite contrasting quantitatively and qualitatively, which present enormous difficulties in blending knowledge from interdisciplinary fields, particularly speech emotion recognition, applied psychology, and human-computer interface. The paper carefully identifies and synthesizes recent relevant literature related to the SER systems’ varied design components/methodologies, thereby providing readers with a state-of-the-art understanding of the hot research topic. Furthermore, while scrutinizing the current state of understanding on SER systems, the research gap’s prominence has been sketched out for consideration and analysis by other related researchers, institutions, and regulatory bodies.